School Psychology and Childhood - a public school experience - Silvia Maria Cintra da Silva; Viviane Prado Buiatti Marçal; Juliana Macedo Pena; Lívia Andrade Santos; Luciane Guedes Santana de Faria; Luizana Alves de Souza; Patrícia Franco Assunção; Ranyere Mendes Vargas (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
This work reports an activity performed as part of coursework in Psychology class during a school semester which aimed to provide students an effective experience of what public school psychologists do, based on the critical presumptions about Psychology and also aimed to present reflections on the performance of this professional together with children. The proposal involved encounters with teachers and children and the undergraduates were responsible for the preparation and execution of activities under the supervision of professors. The Psychology students highlighted the importance of this practice for their professional training, which provided discussions on key questions such as childhood, education and the impact of School Psychology in the Brazilian educational scope.